PROFIL KETERAMPILAN BERPIKIR KRITIS MAHASISWA DALAM MENGEMBANGKAN PEMBELAJARAN SETS TERINTEGRASI KEARIFAN LOKAL - Shanta Rezkita; Nadziroh Nadziroh; Endah Marwanti (Universitas Sarjanawiyata Tamansiswa, 2017)
The demand of KKNI curriculum in the 21st century is about the equality of learning achievement covering attitudes and values, work ability, scientific mastery, authority and responsibility. For that, PGSD graduates of Sarjanawiyata Tamansiswa University (UST) Yogyakarta are expected to be able to design the learning activities, which is in line with the development of science, and technology, which is on the same time, are able to bring Indonesian cultural value into it. The graduates’ competence are presented in their abilities to develop elementary school learning activities based on the Science Environment Technology and Society (SETS) and integrate local wisdom into it. The purpose of this research is to describe the skills of critical thinking of PGSD students in developing SETS-based learning integrated with local wisdom and also along with the indicators that appear in each skill aspect. This is a type of quantitative descriptive research with non-test data collection techniques, observation, and documentation. While the main instruments are in the form of Student Worksheet (LKM), the observation sheet towards the indicators of critical thinking skills. Data analysis techniques is done by using descriptive statistics interpretation through several answering criteria: very good, good, fair, poor, and very poor which is then the results are presented in the form of tables. The results showed that the average critical thinking ability of PGSD UST students was 69.24% with can be categorized in good criteria. Indicator of every critical thinking skills aspect has appeared, even though some targets of achievements have not been optimally gained yet.